A Whole-Genome Survey and the Mitochondrial Genome of Acanthocepola indica Provide Insights into Its Phylogenetic Relationships in Priacanthiformes - Weihua Mao; Ziyi Xu; Qi Liu; Na Li; Lu Liu; Biyan Ren; Tianxiang Gao; Chuan Liu (Animals)
Acanthocepola indica, a deep-sea snake fish, is primarily found in the Indo-west Pacific region, including India, Korea, Japan, and the South China Sea. The taxonomic classification of A. indica based on morphological characteristics remains inaccurate and unclear. In this study, we utilized next-generation sequencing to generate comprehensive genomic data for A. indica. The estimated genome size of A. indica was 422.95 Mb, with a heterozygosity ratio of 1.02% and a sequence repeat ratio of 22.43%. Our analysis suggested that A. indica is diploid, and the draft genome assembly consists of 1,059,784 contigs with a contig N50 of 1942 bp. We identified a total of 444,728 simple sequence repeats in the genome of A. indica. Furthermore, we successfully assembled the complete mitochondrial genome (16,439 bp) of A. indica, which included 13 protein-coding genes, 22 tRNA genes and 2 rRNA genes. Phylogenetic analysis based on mitochondrial genomes revealed that A. indica is closely related to Acanthocepola krusensternii and Cepola schlegelii, providing evidence that the family Cepolidae belongs to the order Priacanthiformes. Population size dynamics analysis indicated that A. indica experienced a bottleneck effect during the Pleistocene Glacial Epoch, likely due to the changes in glacial cycles and sea level fluctuations since ~800 Kya.